Penerapan Model Jigsaw Learning untuk Mengatasi Kesulitan Belajar PAI di SMPN 4 Kota Solok - Putri, Yuliana; Fitriani, Wahidah (YASIN, 2025)
Learning difficulties in Islamic Religious Education (PAI), particularly in abstract subjects such as akhlak, fikih, and the application of Islamic values in daily life, remain a significant challenge at the junior high school level. This study aims to analyze the effectiveness of the Jigsaw Learning model in addressing learning difficulties and improving student learning outcomes in PAI at SMPN 4 Kota Solok. A quantitative approach with a quasi-experimental design was employed, involving 60 eighth-grade students divided into two groups: an experimental class (using the Jigsaw Learning model) and a control class (using conventional methods). Data were collected through pre-tests, post-tests, classroom observations, and student perception questionnaires. The findings showed an increase in the experimental class’s average score from 67.9 to 86.5, while the control class improved from 68.1 to 76.4. An independent sample t-test revealed a significant difference between the two groups (t = 4.85 > t table = 2.00; α = 0.05). These results confirm that the Jigsaw Learning model effectively enhances conceptual understanding, student collaboration, and active participation in PAI instruction. The study concludes that collaborative learning through peer teaching within group structures fosters deeper comprehension and promotes both individual and social responsibility. The implications highlight the importance of integrating cooperative learning strategies in PAI contexts and recommend the incorporation of digital tools to further support critical thinking and social empathy development among students.